1938
DOI: 10.1017/s0022029900002405
|View full text |Cite
|
Sign up to set email alerts
|

184. The milk of the goat under English conditions

Abstract: An account has been given of observations made for over two years on the composition of the milk of the breeds of goat distributed throughout Great Britain. The average percentages of fat and solids-not-fat in the milk of the breeds, together with their standard errors, are recorded. The frequency with which evening and morning samples fell within specified limits of these constituents is indicated for each breed, and diagrammatically for all goats. Detailed analyses of the milk of each breed are given, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2

Year Published

1941
1941
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
3
6
2
Order By: Relevance
“…The results of Mahieu et al (1977) also indicated considerable seasonal variations in the gross composition of goats' milk. Our results for the first 3-4 months of lactation agree with earlier observations (Knowles & Watkin, 1938;R.0nningen, 1965). However, the pasture period, especially mountain pasture, seems to affect the chemical composition of the milk, and fat content increases markedly during this period, as Skjevdal (1972) also found.…”
Section: Gross Composition and N Distributionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of Mahieu et al (1977) also indicated considerable seasonal variations in the gross composition of goats' milk. Our results for the first 3-4 months of lactation agree with earlier observations (Knowles & Watkin, 1938;R.0nningen, 1965). However, the pasture period, especially mountain pasture, seems to affect the chemical composition of the milk, and fat content increases markedly during this period, as Skjevdal (1972) also found.…”
Section: Gross Composition and N Distributionsupporting
confidence: 93%
“…A gradual decline in fat and SNF to a minimum at about the fourth month of lactation and an increase in fat and SNF towards the end of lactation have been reported (Knowles & Watkin, 1938). The results of Mahieu et al (1977) also indicated considerable seasonal variations in the gross composition of goats' milk.…”
Section: Gross Composition and N Distributionmentioning
confidence: 89%
“…The composition of the milk of Fanny at different times during her experimental period is given in Table 5. For comparison the last column shows the average composition of goat's milk under English conditions (34). In general, the composition of the milk of this goat was superior to the figures given in the final column in that the percentages of fat, non-fatty solids, and lactose and casein number were higher and the chlorides lower than the latter.…”
Section: Milk Compositionmentioning
confidence: 82%
“…are shown in It is of interest that the values for lactose are rather lower for goats than for dairy cows. Mean yields varying from 601 to 1089 kg/lactation or 573 to 888 kg/305 days are disappointing, being up to 20% less than yields for the same breeds reported 50 years ago (Knowles and Watkin, 1938). Over that same period yields for dairy cows have increased by over 50%.…”
Section: Dairy Goats In the Ukmentioning
confidence: 92%